Tiktok Short Video Realization Mode and Business Value Analysis - Fan, Hua (Transactions on Economics, Business and Management Research, 2024)
TikTok short videos not only transform the modes of entertainment and social interaction, but also reveal significant commercial potential. By viewing a brief video lasting just a few seconds, users can quickly form an initial impression of a brand or product. Furthermore, through the sharing capabilities of social networks, this information can disseminate rapidly and broadly, facilitating viral marketing effects. It is evident that TikTok's short video platform has emerged as a crucial tool for enterprises to conduct marketing communications and enhance brand awareness, yielding substantial traffic benefits and commercial value. This article mainly discusses the commercial realization model and commercial value of TikTok short videos. First of all, analyses TikTok's strong commercial potential through diversified realization models such as advertising revenue, user payment, live streaming, etc. Subsequently, evaluate the commercial value of TikTok on the user basis of a large base, as well as the diversified content ecology and accurate recommendation algorithms. At the same time, this article will address the challenges of commercial realization. Finally, optimization suggestions such as improving content quality, optimizing advertising, and innovating e-commerce models are put forward to further enhance TikTok's commercial realization ability and platform competitiveness.